2021
DOI: 10.3390/idr13020050
|View full text |Cite
|
Sign up to set email alerts
|

Potential Misdiagnosis between COVID-19 and Dengue Infection Using Rapid Serological Test

Abstract: The coronavirus disease 2019 (COVID-19) pandemic that has a significant rapid transmission is an international public health concern. Several dengue-endemic countries reported similar clinical and laboratory features between COVID-19 and dengue in the early incubation period, and thus discerning the infection is difficult. As a dengue-endemic country, Indonesia also poses the same challenge during the COVID-19 outbreak. This current study analyzed the IgG and IgM profiles from COVID-19 patients by using a sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…Furthermore, due to the wide array of disease indications and the absence of clear case definitions between COVID-19 and dengue, many instances of dengue went unreported. The clinical presentation of both the diseases are similar in symptoms like fever, muscle or body ache, nausea, vomiting, and others leading to a high possibility for misdiagnosis [ 13 ]. Furthermore, in individuals who present with co-infection with both dengue and COVID-19 at the same time, it may result in death or leave the patient in a vulnerable health situation.…”
Section: Challenges and Effortsmentioning
confidence: 99%
“…Furthermore, due to the wide array of disease indications and the absence of clear case definitions between COVID-19 and dengue, many instances of dengue went unreported. The clinical presentation of both the diseases are similar in symptoms like fever, muscle or body ache, nausea, vomiting, and others leading to a high possibility for misdiagnosis [ 13 ]. Furthermore, in individuals who present with co-infection with both dengue and COVID-19 at the same time, it may result in death or leave the patient in a vulnerable health situation.…”
Section: Challenges and Effortsmentioning
confidence: 99%
“…Such cross-reactions were expected, in line with the recent demonstration of shared antigenic similarity between DENV and SARS-CoV-2, resulting in cross-reactivity of the antibody response to both viruses [36][37][38][39][40][41][42][43]. Cross-reactivity of antibodies against DENV and SARS-CoV-2 was shown to be especially high using rapid diagnostic tests (RDT), as opposed to ELISA [36,[38][39][40][41][42][43]. This might explain the relatively low cross-reactivity rates with SARS-CoV-2 samples observed in this study using the VIDAS ® Anti-DENV IgM and IgG assays.…”
Section: Discussionmentioning
confidence: 68%
“…Cross-reactivity with samples from SARS-CoV-2-infected patients (2/16 [12.5%] for IgM and 1/20 [5.0%] for IgG) was also observed. Such cross-reactions were expected, in line with the recent demonstration of shared antigenic similarity between DENV and SARS-CoV-2, resulting in cross-reactivity of the antibody response to both viruses [3643]. Cross-reactivity of antibodies against DENV and SARS-CoV-2 was shown to be especially high using rapid diagnostic tests (RDT), as opposed to ELISA [36,3843].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Dengue NS1 and IgM/IgG RDTs are useful in the emergency room to guide clinicians. However, several studies in Indonesia have reported detection of dengue antibodies in confirmed COVID-19 patients (13,21,23,31), and cross-reactivity between DENV and COVID-19 antibody RDTs has been suggested based on similarities between epitopes in the HR2 domain of the SARS-CoV-2 spike protein and the dengue envelope protein from insilico analysis, though false positives and alternate antigen crossreactivity cannot be ruled out (32). Cross-reactivity between Covid-19 antibodies and other co-circulating infections is also possible (33).…”
Section: Discussionmentioning
confidence: 99%